Odpowiedzi

2010-04-14T19:51:25+02:00
A) 2x-1/2(3x-2)=7/4-x
2x-3/2x+1=7/4-x_________/*4
8x-6x+4=7-4x____________/+4x
6x+4=7_________________/-4
6x=3________________/:6
x=1/2

b) 3x-2(1-2x)=0,5(3x+1,5)
3x-2+4x=1,5x+0,75_________/-1,5x
5,5x-2=0,75____________/+2
5,5x=2,75______________/:5,5
x=0,5

c) 3 1/3x+8=4 2/5x-8
10/3x+8=22/5x-8__________/*15
50x+120=66x-120___________/-66x
-16x+120=-120_____________/-120
-16x=-240_______/:(-16)
x=15

d) x/2+x/4+x/5=x-1__________/*20
10x+5x+4x=20x-20___________/-20x
-x=-20
x=20
1 1 1
2010-04-14T19:54:45+02:00
A) 2x-1/2(3x-2)=7/4-x
2x-1,5x+1=1,75-x
0,5x+1=1,75-x /+x
1,5x+1=1,75 /-1
1,5x=0,75 /:1,5
x=7,5:15
x=0,5
b) 3x-2(1-2x)=0,5(3x+1,5)
3x-2+4x=1,5x+0,75
7x-2=1,5x+0,75 /-1,5x
5,5x-2=0,75 /+2
5,5x=2,75 /:5,5
x=0,5
c) 3 1/3x+8=4 2/5x-8 /-8
3 1/3x=4 2/5x-16 /-4 2/5x
3 1/3x-4 2/5x=-16
3 5/15x- 4 6/15=-16
-1 1/15x=-16 /: (-1 1/15)
x=-16* (-15/16)
x=15
d) x/2+x/4+x/5=x-1 /*20
10x+5x+4x=20(x-1)
19x=20x-20 /-20x
-x=-20 /:-
x=20
1 5 1
2010-04-14T20:02:16+02:00
A) 2x-1/2(3x-2)=7/4-x
2x-1,5x+1=7/4-x
2x-1,5x+x=7/4-1
1/2x=3/4 /:1/2
x=3/4*2/1
x=6/2
x=3/2
x=1 i1/2

b) 3x-2(1-2x)=0,5(3x+1,5)
3x-2+4x=1,5x+0,75
3x+4x-1,5x=0,75+2
5,5x=2,75 /:5,5
x=0,5
c) 3 1/3x+8=4 2/5x-8 /-8
3 1/3x=4 2/5x-16 /-4 2/5x
3 1/3x-4 2/5x=-16
3 5/15x- 4 6/15=-16
-1 1/15x=-16 /: (-1 1/15)
x=-16* (-15/16)
x=15

d) x/2+x/4+x/5=x-1
x/10x/20+5x/20+4x/20=x-1
19/20x=x-1
-x+19/20x=-1
-1/20x=-1 /:-1/20
x=-1*-20/1
x=20
1 1 1